Effects of topdressing of silicon fertilizer on stress resistance and yield of rice under reduced pesticide application - WU Yixin; HUANG Qiwei; YE Mujun; LIANG Yongchao; PENG Hongyun (浙江大学学报. 农业与生命科学版, 2021)
A field experiment was carried out on ‘Zheyou 21’ rice cultivar, and the effects of topdressing of silicon (Si) fertilizer on stress resistance and yield of rice were studied at two levels of pesticide application. The normal level of pesticide application (375 g/hm2 75% tricyclazole wettable powder, D1) and the reduced level of pesticide application (225 g/hm2 75% tricyclazole wettable powder, D2) were set up. Each level of pesticide application contained two Si fertilizer treatments, including non-topdressing of Si fertilizer (－Si) and topdressing of Si powder fertilizer (750 kg/hm2, ＋Si). The results showed that compared with －Si, the ＋Si increased the breaking resistance of the second stem by 26.71%, and reduced the lodging index by 13.29%, incidence of rice ear neck blast by 15.37%, disease index by 19.09%, and increased yield by 3.33% (P＜0.05) of rice under the treatment of D1. Compared with －Si, the ＋Si increased the breaking resistance of the second stem by 33.67%, and reduced lodging index by 14.04%, incidence of rice ear neck blast by 28.98%, disease index by 23.11%, and increased yield by 11.44% (P＜0.05) of rice under the treatment of D2. In conclusion, topdressing of Si fertilizer could reduce lodging index and disease index of rice ear neck blast, leading to enhance lodging resistance and disease resistance to rice ear neck blast, and increase rice yield under the reduced level of pesticide application. In the case of no Si topdressing, rice yield was reduced due to the reduction in pesticide application, while in the case of Si topdressing, there is no significant effect on rice yield.